Examining Inclusive Tertiary Education Delivery through the National Open University of Nigeria's Community Study Centres - Oyebode, Musibau O. (West African Journal of Open and Flexible Learning, 2024)
Conventional universities in Nigeria can no longer absorb the growing population of candidates desiring higher education. National Open University of Nigeria (NOUN) came to the rescue in 2003. With the opening of community study centres across the nation, it is pertinent to gauge access with quality. The study investigated how much access has been provided by NOUN, the adequacy of facilities, the quality of tuition, as well as attrition rate. Using the survey method involving qualitative and quantitative approaches, the instruments of data collection included a set of Likert five scale questionnaire administered to 600 respondents and an interview guide conducted with 24 interviewees selected through snowball and purposive sampling techniques. Statistical records of enrolment, registration and graduation were also analysed for attrition rate. Using Charles Wedemeyer’s theory of independent study, findings revealed that certain barriers to gaining access to tertiary education are overcome as 87.3% of the respondents believed that NOUN provides adequate access. 56.5% of the respondents adjudged NOUN facilities as inadequate while 76.5% of the respondents opined that online facilitation, video lectures and quality course materials provide good tuition. The attrition rate over six years is 41% due to personal, motivational and institutional challenges. It was concluded that though NOUN is adding value to university education in Nigeria through access and service delivery, a lot of gaps still exist. Although the community study centres are viable and have the capacity for sustenance, the government and communities need to continue collaboration with NOUN to improve their services.Résumé : Les universités conventionnelles du Nigeria ne peuvent plus absorber la population croissante des élèves qui quittent l'école secondaire et désireux de faire des études supérieures. L'Université Nationale Ouverte du Nigeria (NOUN) est venue à la rescousse en 2003. Avec l'ouverture récente d'un plus grand nombre de centres d'études communautaires à travers le pays, il est pertinent d'évaluer l'accès et la qualité. Les objectifs de l'étude étaient d'examiner le degré d'accès à l'enseignement universitaire fourni par NOUN, l'adéquation des installations pour l'enseignement et l'apprentissage, la qualité des cours ainsi que le taux d'attrition. À l’aide d’une méthode d’enquête faisant appel à des approches qualitatives et quantitatives, les instruments de collecte de données comprenaient un ensemble de questionnaires à cinq échelles de Likert administrés à 600 répondants et un guide d’entrevue mené auprès de 24 entretiens avec 24 personnes interrogées sélectionnées à l’aide de techniques d’échantillonnage ciblé et analysé. Les statistiques relatives aux inscriptions, aux inscriptions et aux diplômes ont également été analysées pour déterminer le taux d’attrition. En utilisant la théorie de l'étude indépendante de Charles Wedemeyer, les résultats ont révélé que certains obstacles à l'accès à l'enseignement supérieur sont surmontés car la majorité des personnes interrogées (87,3 %) pensent que les programmes académiques et professionnels de NOUN offrent un accès adéquat à l'enseignement supérieur. 56,5 % des personnes interrogées jugent les installations de NOUN inadéquates. Au total, 76,5 % des personnes interrogées estiment que la facilitation en ligne, les cours vidéo et les supports de cours de qualité sont utilisés pour combler les lacunes des cours en face à face, ce qui permet de dispenser un enseignement de qualité. Le taux d'attrition sur une période de six ans est élevé (41 %) en raison de difficultés personnelles, motivationnelles et institutionnelles. Bien que, les centres d’études communautaires sont viables et ont la capacité de perdurer, le gouvernement et les communautés doivent continuer à collaborer avec NOUN pour améliorer ses services.Mots-clés : accès, facilitation matériel de cours centres d'études, universités
Keywords: Access; facilitation; course materials; study centres; universities